MANTHUQ DAN MAFHUM DALAM STUDI ULUM AL-QUR’AN DAN ILMU USHUL FIQIH - Isnan Ansory; Muhammad Yusuf Siddik; Derysmono (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2024)
This research aims to find out the description of the concepts of manthuq and mafhum in the study of al-Qur'an science and Ushul Fiqh science as well as to find common ground and differences between the two. The research method used is library research method with descriptive qualitative analysis technique. The concept of manthuq and mafhum as an approach in understanding the content of the Qur'an is one of the knowledge that must be known by Qur'anic scholars, especially in the legal aspect. Because the lafaz al-Qur'an opens space to be understood explicitly or implicitly, and this is where the flexibility aspect of Islamic law that is based on the Qur'an can be found, to continue to be relevant to the demands of the times. Based on the results of this research, it can be concluded that there is no fundamental difference between the literature of al-Qur'an and Ushul Fiqh in describing the concepts of Manthuq and Mafhum. Although from the aspect of foundation, thought patterns and details of the discussion, Ushul Fiqh literature seems to have a larger portion than the literature of Ulum al-Qur'an. This is because the methods of Ushul Fiqh also function as methods in understanding the Qur'an itself. Even if it is drawn to its source, basically Islamic sciences are a unity, which until because of the demands of the times polarized into various Islamic studies.